FM radio: family interplay with sonic mementos - Petrelli, Daniela; Villar, Nicolas; Kalnikaite, Vaiva; Dib, Lina; Whittaker, Steve (Proceedings of the 28th international conference on Human factors in computing systems, 2010)
Digital mementos are increasingly problematic, as people acquire large amounts of digital belongings that are hard to access and often forgotten. Based on fieldwork with 10 families, we designed a new type of embodied digital memento, the FM Radio. It allows families to access and play sonic mementos of their previous holidays. We describe our underlying design motivation where recordings are presented as a series of channels on an old fashioned radio. User feedback suggests that the device met our design goals: being playful and intriguing, easy to use and social. It facilitated family interaction, and allowed ready access to mementos, thus sharing many of the properties of physical mementos that we intended to trigger.